2003
DOI: 10.1083/jcb.200212136
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans p120 catenin homologue, JAC-1, modulates cadherin–catenin function during epidermal morphogenesis

Abstract: The cadherin–catenin complex is essential for tissue morphogenesis during animal development. In cultured mammalian cells, p120 catenin (p120ctn) is an important regulator of cadherin–catenin complex function. However, information on the role of p120ctn family members in cadherin-dependent events in vivo is limited. We have examined the role of the single Caenorhabditis elegans p120ctn homologue JAC-1 (juxtamembrane domain [JMD]–associated catenin) during epidermal morphogenesis. Similar to other p120ctn famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
151
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 32 publications
5
151
0
2
Order By: Relevance
“…Davis et al (Davis et al, 2003) also discussed that murine p120KO is embryonic lethal. On the other hand, experiments in C. elegans and Drosophila indicated that p120 is not essential in these organisms (Myster et al, 2003;Pettitt et al, 2003). Moreover, recent reports indicated that conditional KO of p120 in mouse epidermis and salivary gland caused severe defects in inflammatory response and cell differentiation, respectively, but not cellular lethality Perez-Moreno et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al (Davis et al, 2003) also discussed that murine p120KO is embryonic lethal. On the other hand, experiments in C. elegans and Drosophila indicated that p120 is not essential in these organisms (Myster et al, 2003;Pettitt et al, 2003). Moreover, recent reports indicated that conditional KO of p120 in mouse epidermis and salivary gland caused severe defects in inflammatory response and cell differentiation, respectively, but not cellular lethality Perez-Moreno et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that only cadherins can target p120 catenin to the plasma membrane (Thoreson et al, 2000), and membrane localization of p120 catenin is sufficient to induce its phosphorylation (Xia et al, 2006b). Deletion of p120 catenin in Caenorhabditis elegans resulted in germline cytokinesis defects and sterility (Pettitt et al, 2003;Skop et al, 2004), whereas a loss-of-function study in D. melanogaster, which only contain p120 catenin and not other members of this protein family, showed that p120 catenin is not an essential component of the adherens junction (Myster et al, 2003). As discussed above, this is in sharp contrast to studies in mammals, which suggest that p120 is indispensable for adhesive function.…”
Section: A Cell-cell Actin-based Adherens Junctionsmentioning
confidence: 99%
“…p120 catenin (p120ctn), which binds to the E-cadherin juxtamembrane domain (JMD), can regulate cadherin-mediated adhesion (Aono et al, 1999;Thoreson et al, 2000) by a mechanism that appears to involve cadherin transport and stabilization at the membrane (Ireton et al, 2002;Chen et al, 2003;Davis et al, 2003;Xiao et al, 2003). Surprisingly, the p120ctn gene is not required for invertebrate development (Myster et al, 2003;Pettitt et al, 2003), but recent studies using a depletion-rescue strategy in Xenopus indicate an essential role for p120ctn in early development possibly through an interplay with Rho GTPases (Fang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%